ANALISIS HARGA, IMPOR, DAN EKSPOR SUSU - Haris Budiyono (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2008)
In mid of2007, world market prices for milk powder and other milk products have increased dramatically, reaching levels about double those observed only at six months earlier. Both supply and demand side factors played a role in this sharp elevation on world dairy prices. A direct effect was the increasing prices of various milk products in domestic market, since the milk products manufacturers in the country use about 75 % raw materials from those imported SMF and FCM. This article analyzed the situation of supply and demand side in domestic market, including the impact of world dairy prices on fresh milk those produced by localfarmers